2008
DOI: 10.1111/j.1445-6664.2008.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Introducing an abundance index for assessing weed flora in survey studies

Abstract: This study was carried out to propose a simple abundance index (AI) of weed species, to describe the ranking of weeds in weed communities, and to evaluate weed flora. Based on a 4 year weed survey program conducted in Tehran province, the Thomas methodology for determining the relative abundance (RA) in weed communities was applied and a new, improved method (called the AI method) was introduced. Sixty-one irrigated wheat fields were selected using a stratified sampling procedure.The boundaries of each county … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Thomas (1985) introduced weed relative abundance (RA), which is estimated by summing relative frequency, relative uniformity, and relative density so as to assess weed importance. Moeini et al (2008) proposed the abundance index (AI) in order to introduce a methodology capable of demonstrating the compatibility of weeds with soil and climatic conditions that other indexes failed to show until then. Furthermore, this index evaluates the weed populations and describes the weed ranking in an area.…”
mentioning
confidence: 99%
“…Thomas (1985) introduced weed relative abundance (RA), which is estimated by summing relative frequency, relative uniformity, and relative density so as to assess weed importance. Moeini et al (2008) proposed the abundance index (AI) in order to introduce a methodology capable of demonstrating the compatibility of weeds with soil and climatic conditions that other indexes failed to show until then. Furthermore, this index evaluates the weed populations and describes the weed ranking in an area.…”
mentioning
confidence: 99%
“…Identification of weed distribution can be a significant point in the weed control in the common barley production. Monitoring weeds in the studied areas will help to define the implementation of appropriate management preventions (Moeini et al 2008). Veisi & Moeini (2015) found that C. arvense and C. depressa species, also Avena, Galium, and Vicia, a genus which is the prominent weeds in Kermanshah common barley areas, observed in the Diyarbakir too, this indicates that these weeds can be a trouble in different ecosystems.…”
Section: Resultsmentioning
confidence: 98%
“…Mean field density (MFD), frequency (F) and uniformity (U) were the only quantitative measures used for abundance index (AI) determination (Moeini et al, 2008 Abundance Index (AI k ) = MFD k + F k + U k…”
Section: Discussionmentioning
confidence: 99%
“…High value of MFD of species illustrate it has more competitive ability than other species, while the high value of Frequency and Uniformity characterize its compatibility with the soil and climate conditions (Moeini et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation